ENSINO DE GEOGRAFIA COM O USO DE FILMES NO BRASIL - Moreira, Tiago de Almeida (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2012)
The paper makes a review about Geography teaching using movies on Brazil, presenting eleven works about the theme. Is also presented an inventory of movies relative by the Geography. By this are make discussions that shows there are some difficulties to use movies on the schools but are big possibilities too. This is a theme who have a few of researches on Brazil and this work brings an initial contribution to the question.